Pengaruh Penggunaan LKPD Berdiferensiasi terhadap Hasil Belajar Siswa pada Materi Bangun Ruang - Puspita, Adinda; Rismawati, Rismawati (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to examine the effect of using differentiated Student Worksheets (LKPD) on students' learning outcomes in the topic of three-dimensional shapes at SD Negeri 3 Susoh. The issue stems from conventional teaching methods that overlook students' diverse learning styles and interests, resulting in a low understanding of geometric concepts. This research employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest model. The sample consisted of 17 fourth-grade students, grouped according to their learning styles: visual, auditory, and kinesthetic. Data were collected through essay-format pretests and posttests. The Wilcoxon test yielded a significance value of 0.000 (< 0.05), indicating a statistically significant difference between the pretest and posttest results after implementing the differentiated LKPD. The students' average scores increased from 35.76 to 77.65. These findings suggest that the use of differentiated LKPD positively influences students' learning outcomes in geometry, offering a more inclusive and adaptive approach that aligns with learners' individual characteristics.   Keywords: Differentiated LKPD, Learning outcomes, Three-dimensional shapes, Learning styles